Differential Activity of Antioxidants in Testicular Tissues Following Administration of Chlorophytum borivilianum in Gamma-Irradiated Swiss Albino Mice - Vyas, Ruchi; Kesari, Kavindra Kumar; Slama, Petr; Roychoudhury, Shubhadeep; Sisodia, Rashmi (Frontiers in Pharmacology, 2022)
Background: Oxidative stress induced by radiation causes variable expression of antioxidant enzymes in a tissue-specific manner. Testicular tissues carry out the complex process of spermatogenesis, and studies indicate that testicular damages due to irradiation require long-term recovery before complete resumption. Ionizing radiation also causes oxidative stress in tissues, leading to testicular damage. Aims and Objectives: This study measured differential expression of antioxidant enzymes following administration of C. borivilianum root extract (CRB) in response to irradiation-induced oxidative stress. The activity of various important endogenous enzymatic defense systems was evaluated and correlated for strength of association. Materials and method: Two forms of C. borivilianum (CB) extracts [CB alone and CB-silver nanoparticles (AgNPs)] were administered at a dose of 50 mg/kg body weight to Swiss albino male mice for 7 consecutive days. After that, they were irradiated with 6 Gy irradiation and further used to study various parameters of antioxidant enzymes. Results: Results indicate a significant increase in the level of glutathione (GSH) and the activity of GSH-related antioxidant enzymes in irradiated mice treated with CRE and CRE-AgNPs (silver nanoparticles biosynthesized using C. borivilianum root extract) in comparison to non-pretreated ones (groups I and II). Reciprocal elevation was observed in related enzymes, that is, glutathione S-transferase activity (GST), glutathione reductase (GR), and glutathione peroxidase activity (GPx). Elevation in the activity of catalase (CAT) and superoxide dismutase (SOD) was also evident in both the irradiated groups pretreated with CRE-AgNPs. However, expression of CAT in the CRE-treated irradiated group was similar to that of the non-treated irradiated group. Higher association among CAT-SOD, CAT-GPx, and GR-GST was observed. Conclusion: Overall, it was observed that testicular cells post-irradiation in all groups go through intense oxidative stress; however, groups pretreated with CRE or CRE-AgNPs indicated better toleration and resumption of antioxidant capacity. CRE or CRE-AgNPs pretreated non-irradiated groups mostly remained within the control range indicating stimulated expression of antioxidants.